Recovery reimagined – an examination of the relationship between trauma, stress, addiction, (and) the body and the role of embodied Arts therapies - Rall, Tonia (My University, 2021)
This work explores the nature and healing potential of Embodied Arts therapies such as Drama therapy (DT) and Dance-movement therapy (DMT) with specific reference to recovery, in facilitating mind body integration, managing stress and developing recovery resilience. The assumption is that these approaches offer significant healing possibilities in the context of Addiction Disorders, which is something I explore. It is also an examination of the conceptual basis of addiction as it relates to trauma, stress, pain and the body from a neuro-biological perspective. I include an overview of the etiology of addiction, in terms of it stemming from developmental impairment caused by early childhood trauma or negative experiences, that has an influence on the ability of the adult to manage stress and self-regulate emotions. The premise is that suppressed trauma, stress and pain, when not expressed, stays ‘locked in the body’ and addictive behaviours are an attempt to escape the discomfort, the (pain) body, ‘numb out’ or alleviate suffering. Thus, embodied therapeutic practices can offer respite from addiction by facilitating ‘release’ through expression in the body, amongst many other things. Furthermore, by returning to the embodied experience in the present moment and applying ‘body mindfulness’ or ‘embodied’ (in body) awareness, one can delay the addictive impulse, rather than reaching for the ‘quick fix’ to alleviate stress and pain. Moreover, I am examining the biological dimensions of the addiction cycle and body stress system (BSS) because at the core of all addictive tendencies is stress and the inability to manage stress in healthy ways due to developmental deficits. This is examined with reference to how embodied therapies can offer alternative methods of stress relief whilst simultaneously serve to integrate Mind and body and perhaps mitigate addictive urges. The key to recovery is through the body
A research report submitted to the Wits School of Arts in partial fulfilment of the for the degree of Masters of Arts by coursework and research report in the field of dramatherapy, in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2021